Pengaruh Edukasi Self Management terhadap Kualitas Hidup Pasien Kanker Payudara - Nuiva, Uun; Nuraini, Tuti; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the effectiveness of education or self-management programs on the quality of life of breast cancer patients. The method used was a systematic review using a systematic search through the Proquest, Science Direct, and EBSCOhost databases with articles that met the inclusion criteria with publications between 2014 and 2023 as well as an article search technique using the PRISMA scheme stages. The results of the research showed that the search results identified ten articles in which various self-management programs stated that self-management program education had a positive effect on the quality of life of breast cancer patients. The conclusion obtained is that the self-management program can be an effective intervention to improve the quality of life of breast cancer patients. Keywords:, Breast Cancer, Self Management, Quality of Life